Juvenile non-familial bilateral hallux valgus managed with bilateral chevron osteotomy: a case report - Mistri, Sayan; Ramkishan, D.; Chandra P., Sateesh; Neetha, P.; Thulasiram, K. (International Journal of Research in Orthopaedics, 2026)
Juvenile non-familial bilateral hallux valgus is an uncommon presentation of a progressive multiplanar forefoot deformity that may result in significant pain, functional limitation, and cosmetic concern. We report the case of a 17-year-old female who presented with bilateral medial forefoot pain aggravated by footwear and progressive deformity of both great toes over a two-year duration, without any history of trauma or family predisposition. Clinical examination revealed lateral deviation of both halluces with prominent medial eminence and tenderness over the first metatarsophalangeal (MTP) joints. Radiographic assessment demonstrated hallux valgus angles (HVA) of 39° on the left and 34° on the right, with intermetatarsal angles (IMA) of 15° bilaterally, consistent with moderate deformity. The patient underwent bilateral distal chevron osteotomy with medial capsulorrhaphy and Kirschner wire fixation. At one-year follow-up, she achieved complete pain relief, improved footwear tolerance, satisfactory cosmetic correction, and maintained radiographic alignment without recurrence. This case highlights that distal chevron osteotomy is an effective and reliable surgical option for symptomatic adolescent patients with moderate bilateral hallux valgus when appropriately selected and meticulously performed.